Influence of weather and seasonal factors on whitefly dynamics, associated endosymbiotic microbiomes, and Begomovirus transmission causing tomato leaf curl disease: insights from a metagenomic perspective - Sujatha, S.; Sindhura, Kopparthi Amrutha Valli; Koti, Prasanna S.; Hiremath, Shridhar; Muttappagol, Mantesh; Vinay Kumar, H. D.; Shankarappa, K. S.; Venkataravanappa, V.; Reddy, K. M. Srinivas; Reddy, C. N. Lakshminarayana (Frontiers in Microbiology, 2025)
IntroductionBemisia tabaci (Gennadius) is a globally significant agricultural pest, responsible for transmitting over 120 plant viruses, including those from the Begomovirus genus, which contribute to considerable crop losses. The species complex comprises cryptic species, associated with a diverse array of bacterial endosymbionts that play essential roles in host nutrition, virus transmission, and overall host adaptability. These endosymbionts are classified into primary and secondary categories, with primary endosymbionts forming obligatory, long-term associations, and secondary endosymbionts influencing factors such as biotype differentiation and vector competency. Notably, these microbial communities enhance B. tabaci’s capacity to transmit viruses, including the tomato leaf curl virus (ToLCuV), which poses a significant threat to tomato production.MethodsIn this study, we examined the population dynamics of B. tabaci across three major tomato-growing regions in Karnataka, South India, focusing on their seasonal associations with endosymbionts and the incidence of tomato leaf curl disease (ToLCuD). Multiple regression analysis was employed to assess the influence of weather parameters on whitefly populations and disease prevalence. Additionally, we constructed a metagenomic profile to evaluate the effects of geographical location, seasonality, environmental factors, and agricultural practices on the bacterial communities associated with B. tabaci. Species-specific primers were used to validate the presence and diversity of these bacterial communities.ResultsMeteorological data revealed a positive correlation between temperature and B. tabaci populations, which corresponded with an increased incidence of ToLCuD. Genetic characterization of the whitefly identified Asia II-5 and Asia II-7 cryptic species as the dominant forms in the surveyed regions, with Portiera emerging as the most prevalent endosymbiont. A more in-depth analysis of the microbial communities associated with B. tabaci, utilizing 16S rRNA metagenomic sequencing, revealed a dominance of the Proteobacteria phylum. The endosymbiotic bacterial consortium was primarily composed of Candidatus Portiera, Candidatus Hamiltonella, Candidatus Rickettsia, and Candidatus Arsenophonus.DiscussionThe metagenomic analysis revealed a highly diverse array of bacterial communities, with 92% of sequences classified under Proteobacteria, representing a spectrum of microbial types associated with B. tabaci ranging from parasitic and pathogenic to mutualistic. Within this phylum, Alphaproteobacteria were predominant, known for their role as facultative symbionts, while Gammaproteobacteria provided essential nutrients to arthropods, enhancing their survival and fitness. The interplay of continuous and intensive tomato cultivation, elevated temperatures, favorable host plants, and abundant viral inoculum creates an ideal environment for the proliferation of B. tabaci and the widespread transmission of ToLCuD. The presence of diverse cryptic species of B. tabaci, which are efficient viral vectors, further complicates the situation. These findings underscore the urgent need for integrated management strategies globally to control both whitefly populations and ToLCuD, ensuring the protection of tomato crops and the sustainability of farmer livelihoods.